2019
DOI: 10.1093/milmed/usz243
|View full text |Cite
|
Sign up to set email alerts
|

Anemia Screening in Naval Aviation: Is Hemoglobin a Better Indicator Than Hematocrit as the Primary Index?

Abstract: Introduction Because of the rigorous mental and physical health requirements for Naval Aviation, all applicants and designated personnel must meet physical standards, including initial and periodic screening for anemia. Most standards, including for accession to the U.S. Navy, use hemoglobin as the standard marker to screen for anemia. Moreover, previous literature generally supports the assertion that hemoglobin is more reliable and accurate than hematocrit. However, the U.S. Navy Aeromedica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…Second, as we discussed above, in addition to the influence of hemoglobin and other interfering substances, the dilution of serum caused by the release of intracellular substances also leads to hemolysis-induced interference on the analysis of total IgE [13,27,29]. We believe that hematocrit (HCT), an indicator that reflects the proportion of red blood cells in the volume of whole blood, may act as another useful correction factor [33,34]. Regrettably, because of the equipment limitations in our laboratory, the influence of HCT was not investigated in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Second, as we discussed above, in addition to the influence of hemoglobin and other interfering substances, the dilution of serum caused by the release of intracellular substances also leads to hemolysis-induced interference on the analysis of total IgE [13,27,29]. We believe that hematocrit (HCT), an indicator that reflects the proportion of red blood cells in the volume of whole blood, may act as another useful correction factor [33,34]. Regrettably, because of the equipment limitations in our laboratory, the influence of HCT was not investigated in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Hb measurement is relatively inexpensive, and it is considered the most reliable indicator of anemia by the WHO. 1,2 Although hematocrit (i.e., the volume percentage of red blood cells in the total blood volume) is a less accurate anemia marker, 3 it is still used in several countries, and conversion formulas between hematocrit and Hb are available. 3 Many studies have found a direct relationship between anemia and other comorbidities, [4][5][6][7] as well as to higher mortality rates.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 Although hematocrit (i.e., the volume percentage of red blood cells in the total blood volume) is a less accurate anemia marker, 3 it is still used in several countries, and conversion formulas between hematocrit and Hb are available. 3 Many studies have found a direct relationship between anemia and other comorbidities, [4][5][6][7] as well as to higher mortality rates. [7][8][9] Moreover, in preoperative patients, anemia has been linked to poorer surgical outcome rates and to a higher need for red blood cells transfusion.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation